Predominant Lip Print Pattern Found among Female Students and Employees of Peshawar Medical College - Ijaz Mehmood, Muhammad Tariq Azeem, Rizwan Ul Haq, Ikram Ul Haq, Rubina Salma Yasmin, Ahmed Subhani (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study is to determine the predominant lip print pattern found among female students and employees of Peshawar medical college. Design: It was a cross-sectional study. Study Settings: This study was conducted at Forensic Medicine Laboratory of Peshawar Medical College from November 2021 to April 2022. Material and Methods: A total of 107 (74 females, and 33 employees) voluntary participants both students and employees were included in the study. Lip prints were be obtained from them using lipstick and cellophane tape, and studied in the presence of lip print expert. The lip print patterns were classified and frequencies determined. Results: Overall pattern, type V (26.62%) and type III (19.58%) were the most common ones. There was no significant difference between the ethnicity. Conclusion: It might be said that lip prints are distinctive, and that using them to identify people. The results showed that print of any two lips were not matched exactly. The patterns did not reveal any significant variability with regards to gender or ethnicity. Keywords: Lip Prints, Classification, Pattern Types, Cheiloscopy